2012
DOI: 10.1128/aac.00234-12
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Emergence of Tigecycline Resistance in Multidrug-Resistant Klebsiella pneumoniae and Escherichia coli

Abstract: Although resistance to tigecycline has been reported in surveillance studies, very few reports have described the emergence of resistance in vivo. We report two cases of patients with infections due to SHV-12-producing Klebsiella pneumoniae and K. pneumoniae carbapenemase-3 (KPC-3)-producing Escherichia coli, which developed tigecycline resistance in vivo after treatment. The reported limited experience underlines the risk of occurrence of a tigecycline MIC increase under treatment pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Our study found a high rate (9%) of in vivo TR emergence among patients who initially presented with a TS-MDRKP strain in the previous 90 days; exposure to tigecycline was the only independent predictor of subsequent resistance. These results build on and expand our knowledge from several recent case reports that describe the occurrence of TR-MDRKP among patients recently treated with tigecycline monotherapy or combination therapy (7,8,9,10,15). In our study, MDRKP isolation from the urinary tract or other body sites where low tigecycline concentrations are achieved was not associated with emergence of TR.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Our study found a high rate (9%) of in vivo TR emergence among patients who initially presented with a TS-MDRKP strain in the previous 90 days; exposure to tigecycline was the only independent predictor of subsequent resistance. These results build on and expand our knowledge from several recent case reports that describe the occurrence of TR-MDRKP among patients recently treated with tigecycline monotherapy or combination therapy (7,8,9,10,15). In our study, MDRKP isolation from the urinary tract or other body sites where low tigecycline concentrations are achieved was not associated with emergence of TR.…”
supporting
confidence: 60%
“…Thus, the selection of a genetically distinct TR strain that was previously present below detection levels by tigecycline exposure cannot be excluded in our study; however, prior studies using molecular typing methodologies suggest the in vivo emergence of TR in previously drug-susceptible strains upon drug exposure (7). TR is mediated by the overexpression of the efflux pump AcrAB-TolC (17).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…This may explain the lower efficacy in HAP. Fourthly, as tigecycline has been used in clinic for about a decade, Page 11 of 32 A c c e p t e d M a n u s c r i p t 11 tigecycline-resistant strains are emerging with reported isolates of tigecycline-resistant klebsiella pneumonia (37 38), Escheichia coli (38) and acinetobacter baumannii strain (39). Studies that verified higher efficacy of high-dose tigecycline for extremely resistance Gram-negative pneumonia were identified (40).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the use of tigecycline is limited due to lack of controlled studies targeting XDR organisms, concerns regarding efficacy and safety in critically ill patients, as well as the rapid development of resistance. The emergence of resistance via upregulation of efflux pumps during therapy is well described and a matter of concern [32]. The efficacy of tigecycline in clinical trials is related to low MICs, low baseline albumin concentration, lower severity and absence of VAP [33], usually not representing the patient population with XDR infection.…”
Section: Tigecyclinementioning
confidence: 99%